Boosting Productivity and Profitability of Chickpea through Cluster Front Line Demonstration (CFLD) in Churu District of Rajasthan - Ali, Shaukat; Shivran, R. K.; Chandra, Subhash; Gupta, Aditi (International Journal of Bio-resource and Stress Management, 2023)
The present study was conducted during rabi season (October to April) of four consecutive years from 2018–19 to 2021–22 at 175 selected farmer’s field in Dhani Gangajal, Kalana Tal, Bas Mamraj, Bhamra, Nethwa, Sahawa and Dingli villages of Churu District, Rajasthan, India. A total of 175 Cluster Front Line Demonstrations (CFLD) on chickpea was conducted. The farming situation was both irrigated and rainfed while, soil was sandy to sandy loam low in nitrogen, medium in phosphorus and medium to high in potash. Gap assessment was done and on the basis of gap assessment, improved recommended technologies were demonstrated. On four-year average basis, higher grain yield was recorded under demonstration field (1714 kg ha-1) as compared to farmers practices (1379 kg ha-1) which was 24.30% higher than farmer’s practices (Local check). The average extension gap, technology gap and technology index were 336 kg ha-1, 849 kg ha-1 and 20.12%, respectively. The higher average total returns was also recorded in demonstration plot which was ` 86721 ha-1 as compared to farmer’s practices (`Rs. 86721 ha-1). There was no much difference in cost of cultivation for demonstration plot (` 24980 ha-1) and farmers practices (`Rs. 22980 ha-1). An additional investment of `Rs. 2000 ha-1 consists with scientific monitoring of demonstration and non–monetary factors resulted in additional return of ` Rs. 16,939 ha-1. Due to higher additional return farmers got `Rs. 14939 ha-1 as effective gain. On four-year average basis, incremental benefit:cost ratio was recorded 8.45.